Parents’ experiences of living with a child with cancer undergoing hematopoietic stem cell transplantation: a qualitative content analysis study - Maleki, Maryam; Dehghan Nayeri, Nahid; Hamidieh, Amir Ali; Pouraboli, Batool (Frontiers in Psychology, 2024)
Objectives: Pediatric Hematopoietic Stem Cell Transplant (HSCT) profoundly impacts the physical, psychological, and social aspects of parents' lives. Thus, this study aimed to explore the experiences of parents living with a child with cancer who undergoes HSCT.This qualitative study involved 20 parents of children with cancer who were undergoing HSCT at a referral hospital in Iran. Purposive sampling was used to select the participants from February 2023 to November 2023. In-depth semi-structured interviews, featuring open-ended questions, were utilized for data collection. Data analysis was performed using conventional content analysis.Results: Data analysis revealed two main themes. "Surrounded by hardships" and "Selfactualization". The first theme encompassed participants' experiences of facing difficulties in life after being aware of their child's need for HSCT. This theme consisted of four categories: "uncertainty about the child's future," "exhaustion from the child's treatment process," "worrying about the healthy child(ren)," and "helplessness". The second theme "self-actualization" included with two categories: "transformation in life's philosophy" and "acquisition of new capabilities". These categories highlighted the positive outcomes experienced by the participants following their child's HSCT.Our findings underscore the importance of healthcare providers being attuned to parents' experiences throughout their child's HSCT trajectory. It is crucial for healthcare providers to encourage parents to articulate their concerns and feelings and seek support from healthcare providers, family, and friends. The development of psychological support services in healthcare settings can facilitate tailored interventions to alleviate parents' difficulties.